EFEKTIVITAS PROGRAM KELUARGA HARAPAN PADA MASA PANDEMI COVID-19 DI KELURAHAN KEBON JERUK KECAMATAN TANJUNG KARANG TIMUR - Lies Kumara Dewi; Annisa Zahara A.Razak (e-JKPP, 2022)
This research was conducted in Kebon Jeruk Village, Tanjung Karang Timur District on the Effectiveness of the Family Hope Program during the Covid-19 pandemic. This study aims to determine whether the Family Hope Program during the Covid-19 pandemic can be said to be effective or not. The research method used in this research is descriptive research with a qualitative approach, primary and secondary data sources as well as interview, observation and documentation data collection techniques. This study found that the Family Hope Program during the Covid-19 pandemic in Kebon Jeruk Village, Tanjung Karang Timur District could help reduce the burden of community spending, but the Family Hope Program could not be said to be effective as a whole. This is because there are still obstacles in the implementation of the Family Hope Program, namely not all program recipients have communication tools, lack of awareness of program recipients and the implementation of the Family Hope Program during the Covid-19 pandemic is hampered and not routine.